The Particulate Organic Carbon-to-Nitrogen Ratio Varies With Ocean Currents - Xiao, Shengjun; Zhang, Linlin; Teng, Yuhao; Huang, Tao; Luo, Wen (Frontiers in Environmental Science, 2021)
Ocean currents could adjust ocean carbon and nitrogen composition which are an important part of global carbon and nitrogen cycle. We got global concentration of particulate carbon and nitrogen in different depth, classified them according to ocean currents (upper 300m) and analyzed POC:PON ratio (particulate organic carbon to nitrogen ratio) variations. We found that, the regions with currents have higher ratio than without currents in northern hemisphere except in 50°~ 60°N (median ratio without currents is 8.38). Warm currents (median ratio range from 5.96 to 8.44) have higher ratio than cold (6.19 to 8.89) except the East Greenland Current (reach to 8.44) and Labrador Current (reach to 8.89). Meanwhile, we also analyzed the effects of ocean currents’ flowing, and found that the distributions of POC:PON ratio varies in different current types (e.g. cause of formation, distance from shore). Generally speaking, the POC: PON ratio of eolian currents and near-ocean currents change fiercer than that of compensation currents and near-coast currents. Ocean currents also have a buffering effect in variation between surface and deep water, which prevent the severe change of POC: PON ratio. The high value anomaly of POC:PON caused by the confluence of warm and cold currents was also analyzed. It can be deducted that, the high ratio in the high latitude region was mainly caused by the terrigenous organic matter (especially carbon) and the low nitrogen.